A possible Dicraeosaurid Dental Pattern? - Garderes, Juan Pablo (2019)
Cranial remains among Dicraeosauridae are scarce, even more considering remains with dental information (i.e., tooth bearing bones). Only Suuwassea Harris, Dicraeosaurus Janensch, and MMCh-PV 75 (from Bajada Colorada Formation, Neuquén, Argentina) preserved toothbearing cranial remains. Within Diplodocoidea, it was proposed that Dicraeosauridae had the condition of an equal functional teeth number between upper and lower jaws, based on Dicraeosaurus remains, which bears 16 alveoli in each jaw (4 in premaxilla, 12 in maxilla, and 16 in dentary). However, considering Suuwassea, the holotype and referred material stands against this proposal, because the upper jaw presents 11 alveoli (4 in premaxilla, 7 in maxilla) whereas the lower jaw bears 9 alveoli, here assumed to be complete in the alveolar count, despite its general incompleteness. MMCh-PV 75 supports the condition stated of an equal tooth number but with a lower count, showing 12 alveoli in each jaw (4 premaxillary and 8 maxillary teeth preserved as an isolated tooth row, and 12 teeth in articulation with the dentary). It has also been proposed an increase in the number of functional teeth within Dicraeosauridae. Suuwassea was recovered as a basal dicraeosaurid, while Dicraeosaurus being more derived. MMCh-PV 75 is recovered in a more derived position than Suuwassea, but more basal than Dicraeosaurus, thus this would support the incrementation in the number of dental elements along dicraeosaurid evolution.